Influence of cover cropping on water uptake dynamics in an irrigated Mediterranean vineyard - Tomaz, Alexandra (2017)
As a result of its physiological characteristics, vine's yield and quality responses are greatly affected by water availability in the soil. Knowledge about water uptake of grapevines in high water availability pedoclimatic conditions is essential when considering the increasing use of irrigation in a previously rainfed crop. We studied the water uptake of irrigated grapevines under different soil covers. The study was carried out over two years in southern Portugal, a Mediterranean climate region, in 'Aragonez' grapevines installed in Vertisols. A cover crop was sown in half the area while maintaining the permanent resident vegetation in the remaining area. Five levels of annual irrigation supply were applied: 200 mm; 150 mm; 100 mm; 50 mm; no irrigation. Soil moisture was monitored every two or three weeks, and weekly after the irrigation start. Results show that water uptake in the interrows did not cease after the beginning of irrigation. Water uptake by the vines occurred to depths of approximately 3.00 m, hence 7.5 times greater than the cover crop root system depth. Results suggest that over time, the presence of the cover crop forces the vine root system, mainly its thinner roots, to seek water at increasingly deeper soil compartments.